“Uma Guiné Melhor”: the psychological action and the spatialization of population control in rural areas. The strategic villages in Guinea-Bissau between 1968-1973 - Vita, Francesca (Africana Studia, 2024)
In the last decade of colonial Portuguese Guinea (now Guiné-Bissau), the Portuguese government accelerated the process of territory occupation. While colonial administration announced to promote and improve living conditions of the Guinean population, nevertheless the population experienced a violent intrusion in their private and public life by the colonial uthorities. The effective territory occupation and the clash with the rural population started during the War of Independence and especially during the government of Governor General António de Spínola (1968-1972) under the so-called “Uma Guiné Melhor” (“A Better Guinea”) plan. This plan was not only a psychological-propaganda campaign, but also a clear military occupation strategy to achieve the implementation of “strategic camps that imprison” the local population (Ledda, 1970: 119). The aim of this paper is to examine the construction of those strategic camps, to explore the housing typologies and to question the social, spatial and economic impact on the life of the rural Guinean population. This article also aims to frame the controversial messages of the integration policy acclaimed in the “Uma Guiné Melhor” plan by exploring and analysing the strategies of specialization of people in action between 1968-1973. Keywords: Guinea-Bissau, António de Spínola, resettlements, War of Independence.